Immune-related adverse events: A bibliometric analysis - Jiang, Shi-Tao; Liu, Yao-Ge; Zhang, Lei; Sang, Xin-Ting; Xu, Yi-Yao; Lu, Xin (Frontiers in Immunology, 2022)
Background Despite providing clinical benefit, immune checkpoint inhibitors (ICIs) can cause immune-related adverse events (irAEs) in a number of patients. This study explored the development pattern in irAEs research from a bibliometric perspective. Methods We obtained articles and reviews related to irAEs from the Web of Science Core Collection (WoSCC) (retrieved on September 13, 2022). Using the R package "Bibliometrix", the main bibliometric features were calculated, and a three-filed plot was generated to show the relationship between authors, institutions, and topics. VOSviewer was used for co-authorship and keyword co-occurrence analysis and visualization. CiteSpace was used to detect burst references and keywords. Results A total of 3995 publications on irAEs were included. The United States (US), Japan, and China had the highest publications. The Journal for ImmunoTherapy of Cancer had the highest number of publications. In addition to "immune-related adverse events", "immune checkpoint inhibitors", "immunotherapy", and "nivolumab" were the most frequently used keywords. Conclusions A bibliometric analysis of 17 years of irAEs research was conducted to map a basic knowledge structure including countries, institutions, authors, journals, and publications. The findings provided a comprehensive perspective on the broad future of this research area.